Performance of Secondary School Publications in Calapan City: Basis for Campus Journalism Development Plan - Consuelo Untalan; Ma. Arlyn Redublo (Philippine Association of Institutions for Research, Inc., 2019)
Elementary and high schools can run their newspaper publications and Calapan City Division schools have been persistent in producing school papers through the years. This study sought to identify the extent of performance of the secondary school publications of Calapan City Division in terms of providing information to the students, providing information to the parents, and providing information to the community. This study used the descriptive-correlational method. The respondents of this study were the publication staff, school paper advisers, and secondary school heads of eleven (11) secondary at Calapan City Division. A self-structured survey questionnaire was used in gathering data. Results showed that the performance of secondary school publications at Calapan City Division in terms of providing information to the students, parents, and community is to a high extent. This proves that the school publications in the secondary level publish articles relevant to the reading public. The quality of the paper the school publishes depends on the capabilities of writers, the assistance of trained advisers, and the standing of the school publication itself. It is recommended that the school should continue honing the students writing capabilities through training and seminars not only for the sake of scholastic journalism but also to guide them in their career paths.